PENGARUH PERLAKUAN PENCUCIAN DAN PEREBUSAN TERHADAP KADAR RESIDU INSEKTISIDA DAN KARAKTERISTIK SENSORIS PADA SAYURAN KEMBANG KOL (Brassica oleracea var.botrytis L) - Widyantari, N.P.I.; Lani Triani, I G.A.; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
This research were aimed to 1) investigate the effect of washing and boiling time on the levels of residual insecticides profenofos and sensory characteristic on cauliflower 2) to determine an appropriate washing and boiling time for reduing the levels of residual insecticides profenofos and to produce the characteristic of cauliflower that was preferable based on colour, texture, taste and overall acceptance. This research used randomized block design with factorial pattern. The first factor was washing time consists of 3 level namely without washing 0, 15 and 30 seconds process time, The second factor was boiling time consists of 3 level namely time boiling with 1, 2 and 3 minutes process time. Each treatment grouped into 3 groups based on the time implementation, so that obtained 18 unit experiments. Samples tested objectively and evaluation sensory to determine the best treatment, The data analized using ANOVA followed by Duncan test. The result of this research showed that washing and boiling time effected on the levels of residual insecticides profenofos and sensoris characteristic of cauliflower. The treatment combination of washing for 30 seconds and 3 minutes boiling time was the best treatment to reduce residues profenofos contents amount of 0.016 mg/kg and characteristics preferred by the value of the colour 3.85 (yellow bit white-yellow bit green), the texture of 2.35 (rather soft-soft), the taste of 5.85 (between rather like to like), and a 5.75 overall acceptance (between rather like to like).
Keywords: 80